In sickness and health: A reflexive thematic analysis of ethical considerations and experiences of owners of cats treated for diabetes mellitus - Ninni Rothlin-Zachrisson; Bodil Ström Holst; Malin Öhlund; Janeth Leksell; Helena Röcklinsberg (PLoS ONE, 2026)
Cats are widely regarded as beloved family members, with whom owners develop strong emotional bonds. When a cat is diagnosed with diabetes mellitus, many owners choose to pursue medical treatment despite the significant commitment and resources required for disease management. This study qualitatively explored the factors influencing treatment decisions for cats diagnosed with diabetes mellitus, focusing on the emotional, practical, and ethical challenges that shape owners’ choices. In-depth interviews were conducted with 12 cat owners in Sweden, all of whom had opted to initiate treatment for their cats diagnosed with diabetes mellitus. The data were systematically analysed using reflexive thematic analysis, generating three themes within an overarching theme encapsulating key aspects of cat ownership. These themes centered on owners’ perceived responsibility of care, maintaining the cats’ quality of life, and the burden of end-of-life decisions. Findings highlight the interplay of emotional attachment, caregiving responsibilities, and ethical considerations in decision-making. We argue that recognising the emotional bonds between owners and their cats and providing personalised care plans that balance medical needs with owners’ life situations can improve communication, veterinary support and cat welfare. Addressing both the medical and emotional aspects of caregiving is crucial for fostering a sustainable and positive caregiving experience.